TRANSFORMASI DESAIN RUMAH TINGGAL DI PERUMAHAN PADMA RESIDENCE (BANTUL, YOGYAKARTA) SAAT DITEMPATI - Agnes, Gabriella Calista (Universitas Atma Jaya Yogyakarta, 2013)
Abstract: A house is a basic need for every humanâ€™s life. It is not only a place for shelter, but also a place for a family to live, to have social interaction between them, to raise the children, and to give the values of life. Padma Residence is a modern residence which is built by PT. Surya Coco Jaya. Most of its residents make changes to their houses after they occupy it. The main purpose of this study is to observe changes toward the initial design by comparing the initial design and present condition, recording the present condition of the house when it has occupied by determine architectural elements which are changed, determining causal factors of changes, and finding out dominant causal factors toward alteration of architectural elements of the house at Padma Residence, Bantul, Yogyakarta while it is occupied. Methods used in data collecting are literature study and a field survey. A field survey includes observation, interview, and distributing questionnaires to 25 respondents who are the owners of houses in this residence. Data analysis used table which compare the initial design and nowadays condition. The result of data processing and analyzing reveals that the owners do physical changes at their houses while they occupy them, particularly at the front appearance of the house. The changes include the addition of canopies at carport and changes in the layout of the rooms, such as kitchen,Â dining room, and backyard. A dominant factor which has caused those changes is the function of rooms which is added to the house.Keywords: residence, physical changes, the additon of functionAbstrak : Rumah merupakan kebutuhan utama bagi kehidupan setiap manusia. Selain sebagai tempat untuk berlindung, rumah juga merupakan wadah atau tempat manusia atau sebuah keluarga melangsungkan kehidupannya. Perumahan Padma Residence merupakan sebuah hunian modern yang dibangun PT. Surya Coco Jaya dan sebagian besar penghuninya melakukan perubahan pada rumah tinggalnya saat ditempati. Tujuan utama penelitian ini adalah mengetahui perubahan terhadap desain awal rumah tinggal dan kondisi rumah tinggal tersebut saat ditempati dengan mengetahui unsur-unsur arsitektural yang berubah pada desain rumah tinggal saat ditempati di Perumahan Padma Residence, Bantul, Yogyakarta. Metode penelitian dilakukan dengan studi literatur dan survei lapangan. Survei lapangan meliputi pengamatan, wawancara, dan penyebaran kuesioner kepada 25 responden yang merupakan pemilik rumah tinggal di perumahan tersebut. Hasil dari pengolahan dan analisis data menunjukkan bahwa pemilik rumah melakukan perubahan fisik pada rumah tinggalnya saat ditempati, terutama pada tampilan depan bangunan, perubahan yang dilakukan adalah menambahkan kanopi pada carport, peletakan ruang seperti dapur, ruang makan, dan taman belakang. Faktor-faktor yang menjadi penyebab perubahan tersebut adalah pertambahan fungsi ruang.Kata kunci: rumah tinggal, perubahan fisik, pertambahan fungsi